Evaluation of serum concentration of cardiac troponin i in normal racing thoroughbred horses - Javad Tajik; Alireza Sazmand; Seyed Hossein Hekmatimoghaddam; Mohamad Reza Shirazi (Eurasian Journal of Veterinary Sciences)
Aim: Evaluation of serum concentration of cardiac troponin I in racing thoroughbred horses. Materials and Methods: Serum concentration of troponin I was measured in 49 clinically healthy thoroughbred horses using commercial ELISA detection kits. Results: The mean serum concentrations of troponin I was 0.504±0.083 ng/mL (<0.2-1.7 ng/mL), and the median of serum cTnI was <0.2 ng/mL, which was the lower limit of detection. Conclusions: The serum concentration of troponin I measured in horse in Iran was partially different from those of other studies.